P35 Effectiveness of folate receptor-mediated detection (FRD) staining solution for cervical cancer screening. (1st November 2019) - Dai, Y; Wan, L; Moos, D; Li, D
Abstract : Introduction/Background: The detection of HPV infection and Cytology are currently recognized for cervical cancer screening, in many regions there are conditions that make it difficult to establish or maintain high-quality, high-coverage cytology based screening programs. Folate Receptor-mediated Diagnosis (FRD) has been proposed as a reliable method to screen cervical intraepithelial neoplasia and cancer. This study aims to investigate the clinical significance of FRD by comparing the accuracy of FRD with human papillomavirus (HPV) testing and Thinprep cytologic test (TCT). Methodology: From December 2018 to March 2019, patients in the gynecology clinic of the Second Hospital of Jilin University were screened with FRD, TCT, and HPV examinations during the same visit. If any of the three test results were positive, colposcopy was performed with cervical biopsy being the gold standard for pathological diagnosis. Results: The sensitivity of FRD, TCT, and HPV in the diagnosis of cervical intraepithelial neoplasia were 72.22%, 72.22%, and 83.33% respectively. The specificity of FRD, TCT, and HPV in diagnosis was 65.07%, 60.31%, and 25.39% respectively. The accuracy of FRD, TCT, and HPV in diagnosis was 66.67%, 62.96% and 38.27%. The positive predictive value (PPV) of FRD, TCT, and HPV in diagnosis was 37.14%, 34.21% and 38.27% respectively, while the negative predictive value (NPV) was 89.13%, 88.37% and 84.21% respectively. Conclusion: Overall, FRD provided high values of sensitivity, specificity and accuracy. While ensuring high detection rate, FRD has its own unique advantages in detection speed (results in less than 60 seconds), economic cost, and patient compliance. FRD can be a very beneficial and useful tool in the primary screening of cervical intraepithelial neoplasia. Disclosure: Nothing to disclose.